Does public fear that bats spread COVID-19 jeopardize bat conservation?. (February 2021) - Lu, Manman; Wang, Xindong; Ye, Huan; Wang, Huimin; Qiu, Shan; Zhang, Hongmao; Liu, Ying; Luo, Jinhong; Feng, Jiang
Abstract: With >1 400 species, bats comprise the second-largest order of mammals and provide critical ecological services as insect consumers, pollinators, and seed dispersers. Yet, bats are frequently associated with infectious human diseases such as SARS, MERS, and Ebola. As early as the end of January 2020, several virological studies have suggested bats as a probable origin for SARS-CoV-2, the causative agent of COVID-19. How does the public view the role of bats in COVID-19? Here we report pilot data collected shortly after the outbreak of COVID-19 using two online surveys, combined with a conservation intervention experiment, primarily on people who are receiving or have received higher education in China. We found that 84% of the participants of an online survey (n = 13 589) have misunderstood the relationship between bats and COVID-19, which strengthened negative attitudes towards bats. Knowledge of bats, gender, and education level of the participants affected their attitudes towards bats. Participants who indicated a better knowledge of bats had a more positive attitude towards bats. The proportion of female participants who had negative attitudes towards bats was higher than that of male participants. Participants with a higher education level indicated a more positive attitude towards bats after the outbreak of COVID-19. A specially prepared bat conservation lecture improved peoples' knowledge of bats and the positive attitudes, but failed to correct the misconception that bats transmit SARS-CoV-2 to humans directly. We suggest that the way virologists frame the association of bats with diseases, the countless frequently inaccurate media coverages, and the natural perceptual bias of bats carrying and transmitting diseases to humans contributed to the misunderstandings. This probably led to a rise in the events of evicting bats from dwellings and structures by humans and the legislative proposal for culling disease-relevant wildlife in China. A better understanding of the relationship between disease, wildlife and human health could help guide the public and policymakers in an improved program for bat conservation.